Naringin nanoparticles accelerate diabetic rat wound healing by inhibiting oxidative stress - Kurnijasanti, Rochmah; Wardani, Giftania; Mustafa, Mohammad Rais; Anjani, Qonita Kurnia; Sudjarwo, Sri Agus (Edelweiss Applied Science and Technology, 2025)
Diabetic wound healing can be inhibited by oxidative stress due to hyperglycemia. Naringin has strong antioxidant effects. The research was to investigate the antioxidant activity of naringin nanoparticles to accelerate wound healing in diabetic rats injected with streptozotocin. The experimental group consists of healthy control, diabetic control, and three groups of diabetes given a combination of naringin nanoparticles orally at 300 mg/kg BW, and naringin nanoparticles topically at concentrations of 2.5%, 5%, and 10%. Biomarkers indicating oxidative stress, including levels of malondialdehyde (MDA), glutathione peroxidase (GPx), superoxide dismutase (SOD), and the expression of nuclear factor erythroid-derived 2-like 2 (Nrf2), were assessed. On the 14th day post-operatively, an evaluation of skin wound healing was carried out. Oral and topical administration of naringin in nanoparticle form, depending on the dose used, reduced MDA levels, increased SOD and GPx levels, and was proven to increase Nrf2 expression so that it could accelerate the wound healing process in diabetes. Histopathological analysis demonstrated an increase in collagen deposition in the group treated with naringin nanoparticles, correlating with accelerated wound healing. In conclusion, the antioxidant activity of naringin nanoparticles can accelerate the healing process in diabetic wounds by reducing oxidative stress. The results suggest that naringin nanoparticles may be an effective therapeutic option in promoting wound healing for individuals with diabetes.